LEAD EXPOSURE AND POSSIBLE ASSOCIATION WITH VIOLENT CRIMES: A FIELD STUDY IN TWO JORDANIAN PRISONS - Ahed J Alkhatib; Haitham Mohammad Alta'any; Qasem Mohammad Abdelal (European Scientific Journal, ESJ, 2014)
Environment has its impacts on behaviors. One of the major environmental contributors is the environmental exposure to lead. Lead is accumulated in the body and its impacts last for a long time. Several studies have associated crime rates with lead exposure. The objectives of the present study were to investigate lead levels among prisoners in two selected prisons in the Northern of Jordan and to investigate any possible correlation between lead levels and crime related variables. Methodology included visiting two prisons in the northern of Jordan, meeting 46 prisoners, filling a prepared questionnaire, and withdrawing a blood sample from each participant. The study also included 27 participants as a reference group. Blood lead level was measured using Atomic absorption Spectroscopy. Study findings showed that prisoners had a higher blood lead level (0.924+1.79 μg/dl) compared with control group (0.570 +0.560 μg/dl). No significant variation was observed between two study groups (P 0.480). The results revealed positive association between crowded traffic and lead exposure among prisoners (P 0.038). A positive association was also found between blood lead level and monthly income (P 0.000), and number of family members (P 0.000). Taken together, although the study findings showed no significant association between blood lead concentration between prisoners and reference participants, it is observed that prisoners have about double concentration of blood lead and it is highly possible that our findings supported the environmental hypothesis which explained the effects of removal of lead from gasoline in lowering crime rates in US.